Numerical Dust Storm Simulation Using Modified Geographical Domain and Data Assimilation: 3DVAR and 4DVAR (WRF-Chem/WRFDA) - Muhammed Eltahan (IEEE, 2019)
Dust storms have severe environmental, economic, health, weather, and climate change impacts. A severe dust storm that hit Egypt on 22 January 2004 was selected as a case study to establish an accurate numerical model to simulate dust storms over Egypt using the Weather Research Forecast with a chemistry module (WRF-Chem). Two simulation setups using WRF-Chem were conducted using two geographic domains: the first exclusively included dust sources within Egypt, while the second included an external dust source, the Bodélé Depression in southwestern Chad. The first simulation was only able to capture the core of the dust plume from the internal dust source Egyptian Qattara Depression, but the second was able to capture the spatial dust distribution from both the Qattara Depression and the Bodélé Depression. Moreover, the results from our second simulation model had less errors than comparable results using moderate resolution imaging spectroradiometer (MODIS). We then investigated the impact of meteorological data assimilation methods using both three-dimensional and four-dimensional variational assimilation algorithms to simulate the aerosol optical depth of the dust storm using weather research forecast data assimilation (WRFDA) framework.